Endomembrane-Targeting Plasmodiophora brassicae Effectors Modulate PAMP Triggered Immune Responses in Plants - Hossain, Md Musharaf; Pérez-López, Edel; Todd, Christopher D.; Wei, Yangdou; Bonham-Smith, Peta C. (Frontiers in Microbiology, 2021)
Plasmodiophora brassicae is a devastating obligate, intracellular, biotrophic pathogen that causes clubroot disease in crucifer plants. Disease progression is regulated by effector proteins secreted by P. brassicae. Twelve P. brassicae putative effectors (PbPEs), expressed at various stages of disease development (0, 2, 5, 7, 14, 21 and 28 days post inoculation) in Arabidopsis and localizing to the plant endomembrane system, were studied for their roles in pathogenesis. Of the 12 PbPEs, seven showed an inhibitory effect on programmed cell death (PCD) as triggered by the PCD inducers, PiINF1 (Phytophthora infestans Infestin 1) and PiNPP1 (Phytophthora infestans necrosis causing protein). Showing the strongest level of PCD suppression, PbPE15, a member of the 2-oxoglutarate and Fe (II)-dependent oxygenase superfamily and with gene expression during later stages of infection, appears to have a role in tumorigenesis as well as defense signaling in plants. PbPE13 produced an enhanced PiINF1-induced PCD response. Transient expression, in N. benthamiana leaves of these PbPEs minus the signal peptide (∆spPbPEGFPs), showed localization to the endomembrane system, targeting the endoplasmic reticulum (ER), Golgi bodies and nucleo-cytoplasm, suggesting roles in manipulating plant cell secretion and vesicle trafficking. ∆spPbPE13GFP localized to plasma membrane lipid rafts with an association to plasmodesmata, suggesting a role at the cell-to-cell communication junction. Membrane relocalization of ∆spPbPE13GFP, triggered by flagellin N-terminus of Pseudomonas aeruginosa (flg22 - known to elicit a PAMP triggered immune response in plants), supports its involvement in raft-mediated immune signalling. This study is an important step in deciphering P. brassicae effector roles in the disruption of plant immunity to clubroot disease.